2003
DOI: 10.1113/jphysiol.2002.027375
|View full text |Cite
|
Sign up to set email alerts
|

Orthologous myosin isoforms and scaling of shortening velocity with body size in mouse, rat, rabbit and human muscles

Abstract: Maximum shortening velocity (V0) was determined in single fibres dissected from hind limb skeletal muscles of rabbit and mouse and classified according to their myosin heavy chain (MHC) isoform composition. The values for rabbit and mouse V0 were compared with the values previously obtained in man and rat under identical experimental conditions. Significant differences in V0 were found between fibres containing corresponding myosin isoforms in different species: as a general rule for each isoform V0 decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
254
3
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(287 citation statements)
references
References 54 publications
(86 reference statements)
29
254
3
1
Order By: Relevance
“…Hill (1950) predicted that shortening velocity should scale as an allometric function of the body mass, with small animals possessing faster, more powerful muscles. Toniolo et al (2004) showed the scaling relation between V o and body mass and they showed that pig slow fibres conform to the values expected from the scaling equation obtained with other animal species (Pellegrino et al 2003). The resulting values concerning fast fibres were higher in the pig than those obtained in human fibres and similar to those of rabbit fibres (Pellegrino et al 2003).…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Hill (1950) predicted that shortening velocity should scale as an allometric function of the body mass, with small animals possessing faster, more powerful muscles. Toniolo et al (2004) showed the scaling relation between V o and body mass and they showed that pig slow fibres conform to the values expected from the scaling equation obtained with other animal species (Pellegrino et al 2003). The resulting values concerning fast fibres were higher in the pig than those obtained in human fibres and similar to those of rabbit fibres (Pellegrino et al 2003).…”
Section: Discussionsupporting
confidence: 66%
“…The values of P o and V o obtained for the muscle fibres can be compared with published data obtained in other animal species (Pellegrino et al 2003). We found that isometric tension of FOG fibres was not significantly different from that measured in corresponding fibres of other animal species; both slow fibres and fast twitch glycolytic fibres exhibit lower tension values.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The amino acid sequence for MHC-1 of mammals is ϳ80% identical to MHC-2 within the motor domain and for a discussion of the structural and functional differences between MHC-1 and MHC-2 see Ref. 41. The myosin light chains also differ between fast and slow muscle myosins but are generally regarded as having a modulatory role on the properties of the MHC (42).…”
Section: Discussionmentioning
confidence: 99%
“…In the region of MHC isoforms, four bands were separated that corresponded, in order of migration from the fastest to the slowest, to MHC-1 (or slow), MHC-2B, MHC-2X and MHC-2A (or fast). Densitometric analysis of these isoforms were performed to establish the relative proportion of the MHC isoforms identified in the sample [38].…”
Section: Analysis Of Mhc Isoforms Contentmentioning
confidence: 99%